Journey to the Alamo - Cuate, Melodie A. (Book collections on Project MUSE., 2006)
When the new seventh-grade history teacher brings a mysterious trunk to class, Jackie, Hannah, and her brother Nick find themselves transported to the Alamo, where they experience the famous siege first-hand.